Review of HIV testing recommendations in Australian specialty guidelines for HIV indicator conditions: a missed opportunity for recommending testing?. Issue 3 (5th March 2020) - Lin, Yi Dan; Eades, Laura; Nair, Ajit; Korman, Tony M.; Woolley, Ian
Abstract: Background: Australian National human immunodeficiency virus (HIV) Testing policy recommends HIV indicator condition‐based testing, adapted from the European AIDS Clinical Society (EACS) guidelines. Aim: To evaluate the extent that Australian non‐HIV specialty guidelines mention and recommend HIV testing in HIV indicator conditions. Methods: EACS guidelines were reviewed to produce a list of 24 AIDS‐defining conditions (ADC) and 31 indicator conditions (IC) where HIV prevalence >0.1%, and 5 IC where HIV non‐diagnosis would have adverse effect on patients' management. Australian guidelines for these conditions were identified from websites of specialty societies, electronic Therapeutic Guidelines, National Health and Medical Research Council (NHMRC), state governments, MEDLINE and Google searches. We identified eight key IC as that were part of the HIDES I study. Results: Overall, 51 ADC and IC had Australian guidelines: 24/51(47%) mention association with HIV and 14/51 (27%) recommend HIV testing. Twenty‐five out of 51 (49%) Australian guidelines were for ADC: 18/25(72%) mention association with HIV and 5/25 (20%) recommend testing. Twenty‐five out of 51 (49%) were guidelines IC with HIV prevalence of 0.1%: 6/25 (24%) mention HIV association and 8/25 (32%) recommend HIV testing. Two of eight (25%) key IC had no Australian guidelines and 3/8 (38%) do not mention HIV association or recommend HIV testing. Conclusions: Although almost half of HIV non‐HIV guidelines for ADC and IC mention HIV association, only 27% specifically recommend HIV testing. This suggests partnership with guideline development and specialist groups may be useful to ensure patients diagnosed with ADC/IC are tested for HIV.